Code timing estimation and multiuser detection for CDMA systems - Ye, Getian. (2008)
Direct-sequence code-division multiple access (DS-CDMA) technology is attractive as a popular multiple access scheme for personal, cellular and satellite communica-tion services because of its numerous advantages over time-division multiple access and frequency-division multiple access, including soft capacity, multipath resistant, inherent frequency diversity and interference rejection. This thesis is concerned with DS-CDMA systems operating over an additive white Gaussian noise channel and a multipath fading channel. It covers two different research areas: near-far resistant code timing estimation and multiuser detection.